Archaeological remains from the siege of Madinat Basta (Baza, Spain), by the catholic monarchs in 1489 - García-Pulido, Luis José; Caballero Cobos, Alejandro (My University, 2015)
The Catholic Monarchs (Isabella I of Castile and Ferdinand II of Aragon) besieged the cities of the last Islamic kingdom on the Iberian Peninsula during the War of Granada (1482-1492), until surrender the capital of the Nasrid dynasty, Madinat Garnata and Madina Alhambra. The military campaigns were strategically programmed. A series of cities was chosen so that their fall would cause the surrender of a part of the territory, due to a domino effect. The capture of Madinat Basta (Baza), to the extreme North of the Nasrid kingdom, was seen as an easy target by the strategists of the Catholic Monarchs. However, the battle-hardened defence of the population and the special configuration and territorial layout of the city resulted in one of the hardest sieges of the campaign, lasting from mid-June to the beginning of December, 1489. To achieve this goal they adopted a strategy that Scipio Africanus the Younger had already developed in 133 B.C., when he surrounded the Celtiberian city of Numantia. Around Baza there are archaeological remains of different structures that can be linked to this conflict. In this communication we have analysed the fortification works that could have been built during the Christian siege of 1489, on the basis of the archaeological evidence and the historical written sources.
Keywords: Arquitectura militar; España - Historia - 1568-1570 (Guerra de las Alpujarras); Baza (Granada) - Historia - 1489; Arqueología del conflicto; Guerra de Granada